Gallbladder motility in children with chronic functional abdominal pain - C., Raaghul; T., Rajesh N.; Kanagaraju, Vikrant; Elangovan, Bharathi (International Journal of Contemporary Pediatrics, 2019)
Background: Chronic abdominal pain is a common gastrointestinal symptom in children that significantly lowers their quality of life. In adults, Gall bladder (GB) hypomotility / dyskinesia is associated with many functional abdominal disorders but there is scarcity of evidence on its role in childhood gastro-intestinal disorders. Aim of the study is to evaluate the GB motility in children with chronic functional abdominal pain (FAP). Methods: Children aged 5-15 years with chronic abdominal pain fulfilling ROME-III criteria and healthy controls were included and all study participants were subjected to ultrasonographic evaluation of the gall bladder volume in fasting state and post - Fatty test meal (FTM) and its ejection fraction was calculated. Results: Sixtysix children including 31 with chronic FAP underwent sonographic evaluation for GB motility. The mean ejection fraction (EF) of cases and controls were 51.72±17.76% and 57.3±23.26% (p value - 0.158). The mean EF of cases with upper abdominal pain and lower/peri-umbilical abdominal pain were 41.7±17.1% and 57.2±15.9% respectively (p value < 0.0001). Increasing BMI had no significant association with GB motility among the participants. Conclusions: There is lack of significant association between children with chronic FAP and GB hypomotility. Children with upper abdominal pain have lesser GB EF, suggesting a possible abnormal GB motility.